1989
DOI: 10.1080/0028825x.1989.10410145
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome studies in someActinidiataxa and implications for breeding

Abstract: Microsporogenesis was studiedin eleven Actinidia taxa including A. deliciosa (kiwifruit) and in an interspecific hybrid. From chromosome counts at meiotic metaphase 1 or diakinesis, eight taxa were classified as diploids and two as tetraploids and A. deliciosa was confirmed as hexaploid. A putative 2n = 2x, 2n = 4x, 2n = 6x, x = 29 basis for the genus is therefore supported. Chromosomes in all taxa were very small. Three diploids and two polyploids analysed for meiotic pairing behaviour were all characterised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 46 publications
(29 reference statements)
0
36
0
2
Order By: Relevance
“…The relationship between nuclear DNA content and reported chromosome number for the Actinidia species tested in this study was significant (r = 0.99), indicating that DNA mass per chromosome might be equivalent across all Actinidia. Correlations have been obtained between DNA content and chromosome number for Brassica hybrids (Fahleson et al 1988) but not within the Rosaceae (Dickson et al 1992 Reports of chromosome number within Actinidia give no indication as to the statistical range of values found that might be expected from counting a number of cells (Zhang & Beuzenberg 1983;Fraser & Harvey 1986;McNeilage & Considine 1989;Watanabe et al 1990). Variation in chromosome number has been reported in plants derived in vitro from the developing seed of interspecific crosses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between nuclear DNA content and reported chromosome number for the Actinidia species tested in this study was significant (r = 0.99), indicating that DNA mass per chromosome might be equivalent across all Actinidia. Correlations have been obtained between DNA content and chromosome number for Brassica hybrids (Fahleson et al 1988) but not within the Rosaceae (Dickson et al 1992 Reports of chromosome number within Actinidia give no indication as to the statistical range of values found that might be expected from counting a number of cells (Zhang & Beuzenberg 1983;Fraser & Harvey 1986;McNeilage & Considine 1989;Watanabe et al 1990). Variation in chromosome number has been reported in plants derived in vitro from the developing seed of interspecific crosses.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome numbers have been reported for only a few species but the data support a polyploid sequence 2n = 2x, 2n = 4x, 2n = 6x with x = 29 (Zhang & Beuzenberg 1983;McNeilage & Considine 1989;Ferguson 1990;Watanabe et al 1990). A. kolomikta ([Maxim.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Αποδείχθηκε ωστόσο αργότερα, πως το εξαπλοειδές είδος A. deliciosa είναι στην ουσία αλλοπολυπλοειδές, με πιθανότερους πρόγονους του το είδος A. chinensis και ένα άλλο διπλοειδές είδος, το οποίο δεν έχει ακόμα ταυτοποιηθεί. Η αλλοπολυπλοειδής φύση του είδους A. deliciosa επιβεβαιώθηκε από τις έρευνες των McNeilage και Considine (1989), οι οποίοι παρατήρησαν ότι το εν λόγω είδος σχηματίζει δισθενή χρωμοσώματα κατά τη μείωση, καθώς και από το γεγονός ότι όταν διασταυρώνεται με διπλοειδή άτομα του είδους A. chinensis, ακολουθείται δισωμική κληρονόμηση στα τετραπλοειδή άτομα που προκύπτουν, σύμφωνα με δεδομένα ισοενζυμικής ανάλυσης (Huang et al, 1997).…”
unclassified